Food Insecurity and Depression Among Adults With Diabetes: Results From the National Health and Nutrition Examination Survey (NHANES). (June 2017) - Montgomery, Joshua; Lu, Juan; Ratliff, Scott; Mezuk, Briana
Purpose: While both food insecurity and depression have been linked to risk of type 2 diabetes, little is known about the relationship between food insecurity and depression among adults with diabetes. Research Design and Methods: Cross-sectional analyses of the National Health and Nutrition Examination Survey (2011-2014), a nationally representative, population-based survey. Analytic sample was limited to adults aged ≥20 with diabetes determined by either fasting plasma glucose (≥126 mg/dL) or self-report (n = 1724) and adults age ≥20 with prediabetes determined by fasting plasma glucose (100-125 mg/dL) or self-report (n = 2004). Food insecurity was measured using the US Food Security Survey Module. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Logistic regression was used to assess the relationship between food insecurity and depression while accounting for sociodemographic characteristics and health behaviors. Results: Approximately 10% of individuals with diabetes and 8.5% of individuals with prediabetes had severe food insecurity in the past year; an additional 20.3% of individuals with diabetes and 14.3% of those with prediabetes had mild food insecurity. Among individuals with diabetes, both mild and severe food insecurity were associated with elevated odds of depression These relationships were similar in magnitude among individuals with prediabetes. Conclusions: Food insecurity is significantly associated with depressive symptoms in people with diabetes and prediabetes. Results point to the need to address economic issues in conjunction with psychosocial issues for comprehensive diabetes care.